Pengukuran Taksiran Berat Janin Saat Bayi Baru Lahir pada Primipara Lebih Akurat Menggunakan Metode Dare’s dan pada Multipara Lebih Akurat Menggunakan Metode Johnson Syahrir - Martini Fairus; Martini Martini; Riyanto Riyanto (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2019)
Background: One way to monitor fetal growth and well-being is by measuring fetal weight estimates to prevent fetal growth disorders. Purpose: The aim of this study is to compare the accuracy of methods of measuring fetal weight estimation in primiparous and multiparous for newborns' weight. Methods: This study used a comparative descriptive design carried out at an inpatient community health center in the Central Lampung region. The research sample consisted of 104 primiparous women and 104 multiparous women who were taken by bivariate consecutive sampling technique using correlation test. Results: The results showed the estimated fetal weight using 5 measurement methods in primipara obtained a correlation of Dare's correlation of 64%, Johnson Tohsach's correlation of 64.1%, Niswander's correlation of 64.1%, and simple method of correlation of 60.4%, and Johnson Syahrir method correlation of 52.2%. Whereas, the multipara obtained the results of the Johnson Tohsach method with a correlation of 78.2%, the Niswander method 76.5%, the Dare's correlation method 71.1%, and the simple method 58.0%. Conclusion: The most accurate measurement of fetal weight estimation of newborn weight in primipara is the Dare's method, whereas in multipara is the Johnson Syahrir method. Health professionals should measure fetal weight estimates in primipara using the Dare’s method and in multipara using the Johnson Syahrir method.